Nomograms incorporating genetic variants in BMP/Smad4/Hamp pathway to predict disease outcomes after definitive radiotherapy for non‐small cell lung cancer - Ju Yang; Ting Xu; Daniel R. Gomez; Xianglin Yuan; Quynh‐Nhu Nguyen; Melenda Jeter; Yipeng Song; Ritsuko Komaki; Ye Hu; Stephen M. Hahn; Zhongxing Liao (Cancer Medicine, 2018)
Abstract Hepcidin is crucial in regulating iron metabolism, and increased serum levels were strongly linked with poor outcomes in various malignancies. Thus, we investigated if genetic variants in the BMP/Smad4/Hamp hepcidin‐regulating pathway were associated with outcomes in patients receiving definitive radiotherapy for NSCLC. Subjects were 664 NSCLC patients who received ≥60 Gy radiotherapy for NSCLC retrospectively identified from a single‐institution database. Potentially, functional and tagging single nucleotide polymorphisms (SNPs) of BMP2 (rs170986, rs1979855, rs1980499, rs235768, and rs3178250), BMP4 (rs17563, rs4898820, and rs762642), Smad4 (rs12456284), and Hamp (rs1882694, rs10402233, rs10421768, and rs12971321) were genotyped by TaqMan real‐time polymerase chain reaction. Cox proportional hazard's analyses were used to assess potential influences of SNPs on overall survival (OS), local‐regional progression‐free survival (LRPFS), progression‐free survival (PFS), and distant metastasis‐free survival (DMFS). Nomogram of each endpoint model was developed using R project. The median patient age was 66 years. Most (488 [73.2%]) had stage III NSCLC. Age, disease stage, receipt of concurrent chemotherapy, and gross tumor volume were independent factors of OS. Hamp rs1882694 AC/CC genotypes were associated with poor OS, LRPFS, PFS, and DMFS in multivariate analyses. Besides, BMP2 rs1979855, rs3178250, and rs1980499 associated with PFS; Hamp rs10402233 and BMP2 rs1979855 associated with LRPFS; BMP2 rs3178250 associated with DMFS after adjustment for clinical factors. After adding SNPs to each model, all the likelihood ratios were increased; the nomograms were improved significantly to predict LRPFS (P < 0.001) and PFS (P < 0.001), and marginally to predict OS (P = 0.056) and DM (P = 0.057). Our nomograms incorporating significant SNPs in the BMP/Smad4/Hamp hepcidin‐regulating pathway could improve the prediction of outcomes in patients given definitive radiotherapy for NSCLC. Intensified follow‐ups would be recommended for patients with unfavorable outcomes identified in nomograms. Due to the rapid developments of targeted therapies and immunotherapies for NSCLC, it is necessary to further validate our findings in patients receiving such treatments.